Kreativitas Berinovasi Pada Guru Seni di Era Digital - Haryadi, Rochmad (STKIP PGRI Ponorogo Press, 2024)
One of the educational resources that needs to be maintained is dance learning. Dance is an art form that involves rhythmic body movements to express feelings, goals, or thoughts. By the time, dance learning needs to use digital-based methods and creations so that students become increasingly interested. This article aims to discuss the importance of dance teachers’ digital competence and creativity in dance learning at school. The type of research used in this article is library research. The data collection technique uses literature data collection. The data then analyzed by using Miles & Hubberman interactive model, consists of the following stages; data presentation, data reduction and conclusion drawing. The research results in this article discuss (1) teacher creativity in dance learning, and (2) factors inhibiting and supporting the development of teacher digital competence.